2022
DOI: 10.1177/17085381221098826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR-663 on atherosclerosis by regulating the proliferation of vascular smooth muscle cells in lipid plaques

Abstract: Objectives Atherosclerosis (AS) is the main cause of coronary heart disease, cerebral infarction, and peripheral vascular disease. microRNAs (miRNAs) are widely distributed in the human body and closely related to the pathological progress of AS. This study probed into the function of miR-663 in AS. Methods The atherosclerotic plaques, cholesterol (CHOL), low-density lipoprotein (LDL), inflammatory factors, and miR-663 expression in ApoE−/− mice on high-fat diet were evaluated. The overexpressing miR-663 adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…More research is required to determine the precise mechanism by which HMGA2 influences Gsk3β phosphorylation. It has been proven in recent years that HMGA2 is involved in the proliferation and growth of VSMCs 54 , 55 and associated with diabetic nephropathy, atherosclerosis, and cancer 37 , 56 , 57 . These findings indicate the key role of HMGA2 in the let‐7d‐5p induced‐activation of GSK3β/β‐catenin pathway, and let‐7d‐5p may represent a novel target for diabetes‐related plaque formation prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“…More research is required to determine the precise mechanism by which HMGA2 influences Gsk3β phosphorylation. It has been proven in recent years that HMGA2 is involved in the proliferation and growth of VSMCs 54 , 55 and associated with diabetic nephropathy, atherosclerosis, and cancer 37 , 56 , 57 . These findings indicate the key role of HMGA2 in the let‐7d‐5p induced‐activation of GSK3β/β‐catenin pathway, and let‐7d‐5p may represent a novel target for diabetes‐related plaque formation prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org (Deng and Li, 2022). In conclusion, miRNAs regulate atherosclerosis through affecting the function of endothelial cells, macrophages, and VSMCs.…”
Section: Figurementioning
confidence: 91%
“…Studies have shown that plaque formation of AS involves a variety of factors, including vascular smooth muscle cells (VSMCs) abnormal proliferation (2,3). Abnormal proliferation of VSMCs is considered to be an important step in the development of AS, which can lead to arterial wall thickening and the formation of lipid plaques (4,5). Therefore, exploring the molecular mechanisms influencing VSMCs proliferation and migration may help us develop potential molecular targets for AS therapy.…”
Section: Introductionmentioning
confidence: 99%